The wedding girl [compact disc, unabridged] - Wickham, Madeleine, 1969- (Macmillan Audio, 2009)
Milly is about to have a highly publicized wedding with her millionaire fiance. However, ten years ago, Milly married Allan, her gay American friend, so he wouldn't be deported from England. Although the wedding was a ruse, Allan refuses to grant her a divorce. Now, with only three days until her real wedding, Milly must convince Allan to sign the divorce papers, before her fiance and all of England learn the truth.